Cuba After Castro Legacies, Challenges, and Impediments - Gonzalez, Edward (RAND Corporation, 2004)
When the end of the Castro era arrives, the successor government and the Cuban people will need to answer certain questions: How is Castro's more than four-decade rule likely to affect a post-Castro Cuba? What will be the political, social, and economic challenges Cuba will confront? What are the impediments to Cuba's economic development and democratic transition? The authors examine Castro's political legacies, Cuba's generational and racial divisions, its demographic predicament, the legacy of a centralized economy, and the need for industrial restructuring.